Aplicação do método biomimético para o recobrimento da liga AZ91 com apatitas para aumento da resistência à corrosão - Ramasco, Bruno Torquato (Universidade Federal de São Carlos, 2015)
In orthopedic medicine and traumatology, the use of implants to help bone reconstitution is very common. They are divided in two groups: Internal and external fixation devices. After bone reconstitution, these components lose their function and therefore must be removed. However, in many cases, due to the cost or patient suffering, the devices are not removed. To avoid this, are under development bioabsorbable alloys that after bone healing degrade and are absorbed by the body, not requiring its removal. Among them, magnesium based alloys are under the spot. Regular magnesium alloys, however, present one main drawback: High corrosion rate, which leads to mechanical properties loss before the bone reconstitution and excessive production of gas hydrogen, leading to the formation of gas pockets, which cause adverse reactions and inhibit bone growth. This study aims to investigate surface coatings on the commercial alloy AZ91 in order to decrease the corrosion rate, making the material suitable for the use as biodegradable implants. Three modified SBF solutions were employed to coat the surfaces with apatites using the biomimetic method. The influences of pre-treatment of the samples in NaOH solution and heat treatment after coating on the electrochemical behavior of produced coatings were investigated. The results showed that the use of biomimetic method using modified SBF solutions was effective to produce apatite phases on the surface of the magnesium commercial alloy AZ91, considered a more suitable bone replacement than HA. The coated samples presented higher corrosion resistance than the uncoated material, as evaluated by electrochemical tests. This behavior was more pronounced for coatings obtained after the use of pre-treatment NaOH solution.
Apatite coatings on magnesium based alloy AZ91 using biomimetic method for improved corrosion resistance
Keywords: Recobrimento apatita; Liga magnésio; Implante bioabsorvível; Biomimético; Resistência à corrosão; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA